Practice of Breast Self-Examination and Knowledge of Breast and Cervical Cancer Screening: A bi-national Survey in Africa - Omotoso, Olabode; Matariek, Ghadier; Omotoso, Elizabeth; Matareek, Amira; Abdul-Rafee, Ghada, Mahmoud; Malakar, Sucheta; Chutia, Nabanita (My University, 2020)
Background: The burden of breast and cervical cancer is increasing exponentially, especially among women in low- and mid-income countries due to late diagnosis, unhealthy lifestyle choices and adoption of western lifestyles. Early detection, hinged on screening uptake is a key to higher survival rate and managing cancer outcome. Despite some improvement noticed in developed countries, the control of these preventable diseases in African countries including Nigeria and Egypt seems insurmountable. Therefore, this study focused on assessing the knowledge and uptake of Nigerians and Egyptians towards breast self-examination (BSE) and breast and cervical cancer screening. Results: A community-based cross-sectional questionnaire was utilized in both countries to obtain 1,006 respondents via a convenient sampling method. The mean age of study participants was 30.43 6.69. About one-third of participants had a good knowledge (> 66 %) of breast cancer screening (423, 42 %), cervical cancer screening (446, 44 %) and BSE practice (363, 36 %). Age range (26 40 years), educational level (tertiary) and marital status were demographic data that influenced knowledge level. Though with a fairly satisfactory knowledge level, the screening uptake among studied population is very poor as only (111, 11 %) had ever been screened and only (22, 2.2 %) ever vaccinated. The major reasons for poor screening uptake were no awareness of where to be screened and no symptoms. Conclusions: Assessing the knowledge and uptake level of African women through studies like this is crucial in identifying the loopholes in the fight against cancer in Africa. More efforts are required in promoting utilization of cancer screening services, HPV vaccination and BSE practice among African women. The media and internet should be leveraged on as they are the major sources of information about cancer among the respondents.
Keywords: breast self-examination; breast cancer screening; early detection; African women; cervical cancer screening; cancer